2019
DOI: 10.1002/cjce.23565
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis characteristics of low‐rank coals based on double‐gaussian distributed activation energy model

Abstract: Pyrolysis is an important technology in the utilization of low-rank coals (LRCs) and is a prerequisite stage for other conversion methods. This study aimed to develop an understanding of the pyrolysis process of LRCs, especially the relationship between the pyrolysis kinetics and the internal chemical structure. The chemical structure parameters of all of the samples were obtained using the Fourier transform infrared spectroscopy (FTIR) method. Thermogravimetric (TG) experiments were conducted at different hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Based on this theory, a triple‐Gaussian DAEM (3‐DAEM) was developed . It was found that 3‐DAEM is more suitable for experimental data when coal samples lose a significant amount of mass in the low temperature range …”
Section: Introductionmentioning
confidence: 99%
“…Based on this theory, a triple‐Gaussian DAEM (3‐DAEM) was developed . It was found that 3‐DAEM is more suitable for experimental data when coal samples lose a significant amount of mass in the low temperature range …”
Section: Introductionmentioning
confidence: 99%